The Effect of Demographic Factors on Consumer Purchase Intention in Buying Television Set in Kathmandu Valley: An Empirical Study - Rai, Bharat (Pravaha, 2020)
The main objective of the research is to identify the impact of demographic factors on purchase intention. The study examine whether there is any significant differences on consumers’ purchase intention of television across gender, age groups and education level. Primary data has been used in the study. The structured questionnaire has been used for collection of primary data. Convenient sampling technique has been used to collect information from the respondents and 394respondents have been taken from customers buying Television in Kathmandu. The sampling location for the research has been allocated in show room, colleges and houses in Kathmandu. Age, gender and level of education have been taken as independent variables and purchase intention has been taken as dependent variable. Percentage has been used to analyze the purchase intention of respondents; independent sample t-test and ANOVA Test have been used to analyze the collected data and to draw valid conclusions by using SPSS. The result of independent sample t-test showed that there is no significant difference on purchase intention between male and female in buying television in Nepalese market. The result of ANOVA Test showed that there is no significant difference on purchase intention among different age groups. But the result of ANOVA Test showed that there is significant difference on purchase intention among different level of education.